Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1093/ajcn/33.4.739
|View full text |Cite
|
Sign up to set email alerts
|

Zinc absorption from composite meals I. The significance of wheat extraction rate, zinc, calcium, and protein content in meals based on bread

Abstract: The absorption of zinc in man from composite meals based on bread was measured with a radionuclide technique using 65Zn and whole-body counting. Bread was made up from wheat flour of 100 and 72% extraction rate. A lower absolute amount of zinc was absorbed from the white bread compared to the absorption from the same amount of wholemeal bread. When the two types of bread were enriched with zinc chloride the absorption was higher from the white bread than from the wholemeal bread. Addition of calcium in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
3

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(91 citation statements)
references
References 0 publications
5
82
1
3
Order By: Relevance
“…Rapidly and almost fully absorbed (about 79 %) in upper part of the gastrointestinal tract of rats fed free compound (601) Small-intestinal phytases have high activity in rats and very much lower activity in human subjects and pigs (217) Fe: 1 -20 % in human subjects fed usual diets (204) Mg: 70 % in rats fed whole-wheat flour (219) 21 -28 % in human subjects fed brown bread diet (602) 50 % in human subjects fed a typical diet (603) 57·6 % in human subjects fed a standard diet (604) Zn: 16·6 % in human subjects consuming wholemeal bread (605) 20 % in adult women consuming whole-wheat tortillas (606) 35 % in rats fed whole-wheat flour (219) 88·9 -94·6 % in rats fed whole-wheat flour (607) 18·5 % in rats fed wheatmeal (608) 60 -82 % in rats fed whole-grain wheat (609) 30 -37 % in rats fed whole-wheat flour chapatti (610) Cu: 62 -85 % in human subjects fed whole-wheat bread (611) 16·3 -16·5 % in rats fed free compound (71,73) Se: 81·1 -84·5 % in rats fed whole-wheat flour (607) 73 -86 % in rats fed whole wheat as compared with sodium selenite (612) 100 % in rats fed whole-wheat flour as compared with sodium selenite (613) P: 41-55 % in human subjects fed brown bread diet (602) Ca: 81·7 % in human subjects fed whole-wheat bread (614) 43 -44 % in rats fed whole-wheat flour chapatti (610) 85·7 -92·8 % in rats fed whole-wheat flour (607) Thiamin (vitamin B 1 ): 91 % in rats fed whole-wheat bread compared with free thiamine mononitrate (100 %)…”
Section: Appendixmentioning
confidence: 99%
“…Rapidly and almost fully absorbed (about 79 %) in upper part of the gastrointestinal tract of rats fed free compound (601) Small-intestinal phytases have high activity in rats and very much lower activity in human subjects and pigs (217) Fe: 1 -20 % in human subjects fed usual diets (204) Mg: 70 % in rats fed whole-wheat flour (219) 21 -28 % in human subjects fed brown bread diet (602) 50 % in human subjects fed a typical diet (603) 57·6 % in human subjects fed a standard diet (604) Zn: 16·6 % in human subjects consuming wholemeal bread (605) 20 % in adult women consuming whole-wheat tortillas (606) 35 % in rats fed whole-wheat flour (219) 88·9 -94·6 % in rats fed whole-wheat flour (607) 18·5 % in rats fed wheatmeal (608) 60 -82 % in rats fed whole-grain wheat (609) 30 -37 % in rats fed whole-wheat flour chapatti (610) Cu: 62 -85 % in human subjects fed whole-wheat bread (611) 16·3 -16·5 % in rats fed free compound (71,73) Se: 81·1 -84·5 % in rats fed whole-wheat flour (607) 73 -86 % in rats fed whole wheat as compared with sodium selenite (612) 100 % in rats fed whole-wheat flour as compared with sodium selenite (613) P: 41-55 % in human subjects fed brown bread diet (602) Ca: 81·7 % in human subjects fed whole-wheat bread (614) 43 -44 % in rats fed whole-wheat flour chapatti (610) 85·7 -92·8 % in rats fed whole-wheat flour (607) Thiamin (vitamin B 1 ): 91 % in rats fed whole-wheat bread compared with free thiamine mononitrate (100 %)…”
Section: Appendixmentioning
confidence: 99%
“…Tres estudios han mostrado que el óxido de zinc y el sulfato de zinc tienen absorciones similares de productos a base de cereales fortificados con zinc (26)(27)(28). Asimismo, los estudios existentes muestran que la fortificación con zinc puede incrementar la ingesta diaria de zinc y la absorción total de zinc (29)(30)(31).…”
Section: Tablaunclassified
“…First, more than half of the zinc in US diets is derived from animal foods, and one quarter of the zinc comes from beef [76]. The bioavailability of zinc from vegetarian diets is also likely to be less than that of non-vegetarian diets because the bioavailability of zinc is enhanced by dietary protein, but plant sources of protein are also generally high in phytic acid, an inhibitor of zinc bioavailability [77]. As commented above, most vegetarian studies including the present study reported that vegetarians had the significantly lower zinc intake than non-vegetarians.…”
Section: Total (N=94)mentioning
confidence: 99%